Release your brilliance - Bailey, Simon T. (Shippensburg, Pennsylvania Sound Wisdom, 2014)
"Brilliance is a decision. It's time to disrupt your current reality and... experience your SHIFT into Brilliance....This book is your roadmap, your call to action; your opportunity to create accelerated results professionally, personally and financially...."
Keywords: Self-actualization (Psychology); Success